Exploring the application of AlN graphyne in calcium ion batteries. (29th August 2022) - Kadhim, Mustafa M.; Shadhar, Mohanad Hatem; Nathir, Israa; Taban, Taleeb Zedan; Noori, Aiyah S.; Almashhadani, Haider A.; Rheima, Ahmed Mahdi; Ebadi, Abdol Ghaffar
Abstract: Destiny functional theory (DFT) calculations are undertaken in order to scrutinize the electrochemical and calcium (Ca) storage characteristics of a graphyne-like aluminum nitride monolayer (G-AlNyen) as an electrode material for Ca-ion batteries (CIBs). The results show that the change in internal energy as well as the cell voltage values for the CIB with the G-AlNyen anode are comparable to others with two-dimensional 2D nano-materials. It is shown that Ca is adsorbed primarily onto the center of a hexagonal and triangular ring of G-AlNyen with absorption energies of −2.06 and −0.42 eV. After increasing the concentration of Ca atoms on G-AlNyen, the adsorption energy as well as the cell voltage decreases. Lower values of 0.15–0.32 eV related to the diffusion barrier confirm that the diffusion of Ca in the 2D nano-sheets is rapid. G-AlNyen shows a maximum theoretical capacity of approximately 869.23 mAh h g −1 . The results are evaluated in terms of charge transfer, structure, energy as well as electronic characteristics and provide insight into the construction of better anode materials with higher capacity for the CIB. Highlights: G-AlNyen@Ca has changed his semiconductor character to metallic character. Investigation of the adsorption and charge transfer of Ca on the G-AlNyen. The diffusion energy of Ca, suggesting fast charging/discharging processes.